Determination of Spatial Pattern of Environmental Consequences of Dams in Watersheds - Myung Sik Cho; Jiaguo Qi (Land, 2023)
Many hydro-dams have been built for beneficial gains, but they are causing numerous unintended negative effects on the environment. The complexity of dam impacts and the insufficient knowledge of developing countries result in many uncertainties in managing land systems and environmental impact assessments (EIAs). Also, considering the consequences beyond the dam sites proved challenging in EIAs. In this context, this paper aims to determine the spatial pattern of the environmental consequences of dams, quantify the distance of impacts, and identify different patterns in both upstream and downstream areas. We considered the hydrological linkage of dams with wetlands in watersheds and the spatial relationship between watersheds to explicate the spatial pattern. Two hundred and ninety wetlands in the Mekong, Salween, and Irrawaddy Basins were categorized into those linked with dams and those without dams, and the hydrological characteristics were statistically compared for two periods (before and after the dam booms) using the Mann–Whitney U test. The watersheds having significant differences were found, and their spatial relationship in terms of location (i.e., upstream and downstream) and distance was determined by utilizing the HydroBASINS’ Pfafstetter coding system. The results indicate that the impacts of dams on downstream areas extend significantly farther than their effects on upstream regions in HydroBASINS level-7 representation. The quantitatively determined spatial patterns on upstream and downstream areas can provide accurate spatial baseline information in land system management and EIA.